An Alternating D1-A-D2-A Conjugated Ternary Copolymer Containing [1,2,5]selenadiazolo[3,4-c]pyridine Unit With Photocurrent Response Up to 1,100 nm - Huang, Xuelong; Lan, Ning; Yan, Yunnan; Hu, Xin; Liu, Shengjian (Frontiers in Chemistry, 2020)
Two narrow band gap conjugated ternary copolymers comprising two electron-rich (donor, D) and one electron-deficient (acceptor, A) moieties regularly alternating along the polymer backbone were designed and synthesized. The polymers with the repeating unit in a D1-A-D2-A manner were constructed by copolymerizing a bisstannyled-D1 (D1 = n-alkyl-substituted cyclopentadithiophene) and a dibromo-monomer (Br-A-D2-A-Br, D2 =branched-alkyl-substituted cyclopentadithiophene, A =[1,2,5]selenadiazolo[3,4-c]pyridine or 5-fluorobenzo[c][1,2,5]selenadiazole) through a palladium-catalyzed Stille polymerization. This approach that enables variations in the donor fragment substituents can not only control the polymer regiochemistry but also the solubility. Two ternary copolymers exhibited absorbance up to near-infrared region along with relatively narrow band gap in the range of 1.02–1.26 eV. The polymeric photovoltaic cells based on CDTPSE/PC61BM show the short circuit density of 1.45 mA cm-2, open current voltage of 0.53 V, and photocurrent spectra response from 300 to 1150 nm under AM 1.5 simulator (100 mW cm-2). It is indicated that it can be potentially applied to near infrared photodetectors.